2013
DOI: 10.3389/fmicb.2013.00084
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome Sequence Analysis of Filamentous Microbial Communities Obtained from Geochemically Distinct Geothermal Channels Reveals Specialization of Three Aquificales Lineages

Abstract: The Aquificales are thermophilic microorganisms that inhabit hydrothermal systems worldwide and are considered one of the earliest lineages of the domain Bacteria. We analyzed metagenome sequence obtained from six thermal “filamentous streamer” communities (∼40 Mbp per site), which targeted three different groups of Aquificales found in Yellowstone National Park (YNP). Unassembled metagenome sequence and PCR-amplified 16S rRNA gene libraries revealed that acidic, sulfidic sites were dominated by Hydrogenobacul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(129 citation statements)
references
References 84 publications
9
118
2
Order By: Relevance
“…Increases in O 2 during the day may in part be responsible for increases in microbial growth of M. yellowstonensis and Hydrogenobaculum, which are both aerobic (Kozubal et al, 2008;Takacs-Vesbach et al, 2013;Jennings et al, 2014). Higher 16S rRNA gene expression levels of Metallosphaera compared to Hydrogenobaculum in both environments ( Figure 5) were consistent with higher relative abundances of Metallosphaera observed previously in the upper ∼1 mm of mature Fe(III)-oxide mats, which also corresponds to the active O 2 -consuming layer (Beam et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Increases in O 2 during the day may in part be responsible for increases in microbial growth of M. yellowstonensis and Hydrogenobaculum, which are both aerobic (Kozubal et al, 2008;Takacs-Vesbach et al, 2013;Jennings et al, 2014). Higher 16S rRNA gene expression levels of Metallosphaera compared to Hydrogenobaculum in both environments ( Figure 5) were consistent with higher relative abundances of Metallosphaera observed previously in the upper ∼1 mm of mature Fe(III)-oxide mats, which also corresponds to the active O 2 -consuming layer (Beam et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…The rod-shaped bacteria Hydrogenobaculum spp. initiate biofilm attachment, and the iron-oxidizing archaea Metallosphaera yellowstonensis (strain MK1) are responsible for the oxidation of Fe(II) and subsequent accretion of Fe(III)-oxides (Macur et al, 2004;Kozubal et al, 2008;Takacs-Vesbach et al, 2013;Jennings et al, 2014;Beam et al, 2016). Oxygen is a key driver of microbial growth and subsequent mat morphology (Kempes et al, 2014), and its diffusion into the mat is the rate-limiting factor for Fe(III)-oxide mat formation (Beam et al, 2016).…”
Section: •−mentioning
confidence: 99%
“…Whereas the second one is represented in seven archaeal-dominated sediments: Nymph Lake (NL; 88°C, pH 4), Monarch Geyser (MG; 78-80°C, pH 4.0), Cistern Spring (CIS; 78-80°C, pH 4.4), Washburn Spring (WS; 76°C, pH 6.4), 100 Spring Plan (OSP_8; 72°C, pH 3.4), and including CH and JCHS described above (Inskeep et al 2013a, b). The diversity detected among sites with similar characteristics suggested that additional geochemical and geophysical factors, such as the total dissolved organic carbon (DOC) and the amount of solid-phases of carbon, could play a role in the consortia composition (Inskeep et al 2013a, b;Takacs-Vesbach et al 2013). A similar observation but mainly related to the different SO 4 2-/Cl -ratio was recently reported in the analysis of three thermal springs sharing pH * 4.0 of the YNP: Norris (NOR; 84°C, pH 4.34), Mary Bay Area (MRY; 80°C, pH 4.32) and Mud Kettles (MKL, 72°C pH 4.35), which resulted exclusively populated by bacteria and dominated by microorganisms belonging to the phylum of Cyanobacteria (NOR and MRY) and Aquificales (MKL) (Jiang and Takacs-Vesbach 2017).…”
Section: Yellowstone National Park Usamentioning
confidence: 99%
“…Microbial communities in these habitats tend to have low diversity (2,4,5) and specialized physiologies (6), suggesting a potentially limited resistance and resilience to change (7). However, few experiments have been conducted in extreme environments to assess the susceptibility of these communities to disturbance.…”
mentioning
confidence: 99%